The law of ESG derivatives : risk, uncertainty and sustainable finance - Arias-Barrera, Ligia Catherine (Routledge, 2024)
"This book weaves together a comprehensive legal analysis of sustainable finance regimes governing Environment, Social and Governance (ESG) derivatives, with insightful sociological perspectives on risks and uncertainties. Sustainable finance offers a unique chance to channel capital towards sustainability goals, with ESG derivatives emerging as potent catalysts for a transition to a more sustainable economy. Beyond amplifying capital flow, they strategically align with effective ESG risk and uncertainty management. The book explores how integrating ESG derivatives can strategically serve sustainable investment, offering insights into optimal risk management. The work not only outlines challenges but presents potential solutions, highlighting ESG derivatives' role in addressing market failures affecting sustainable finance, which is an aspect often overlooked by regulators in the EU, the UK, and the US. Serving as a strategy guide for countries adopting a diverse sustainable finance portfolio, the book targets policy practitioners and advocacy specialists, catering to a broad multidisciplinary audience amid the increasing interest in ESG-related products. The book's dual emphasis on financial derivatives for ESG risk management and sociological perspectives positions it as an ideal resource for scholars, experts, practitioners, researchers, and curious minds across Law, Business, Management, and Sociological Studies"-- Provided by publisher.
Keywords: Finance -- Law and legislation.; Derivative securities -- Law and legislation.; Financial institutions -- Law and legislation.; Investments -- Law and legislation.; Financial risk management.; Sustainable development -- Law and legislation.; elektronické knihy; electronic books